Heparan Sulfate Biosynthesis: Regulation and Variability - Kreuger, Johan; Kjellén, Lena (The journal of histochemistry and cytochemistry, 2012)
Nearly all vertebrate cells have been shown to express heparan sulfate proteoglycans (HSPGs) at the cell surface. The HSPGs bind to many secreted signaling proteins, including numerous growth factors, cytokines, and morphogens, to affect their tissue distribution and signaling. The heparan sulfate (HS) chains may have variable length and may differ with regard to both degree and pattern of sulfation. As the sulfation pattern of HS chains in most cases will determine if an interaction with a potential ligand will take place, as well as the affinity of the interaction, a key to understanding the function of HSPGs is to clarify how HS biosynthesis is regulated in different biological contexts. This review provides an introduction to the current understanding of HS biosynthesis and its regulation, and identifies research areas where more knowledge is needed to better understand how the HS biosynthetic machinery works.